Neofavolus subpurpurascens comb. nov., with new records from the Neotropics - Palacio, Melissa; Silveira, Rosa Mara Borges Da; Robledo, Gerardo Lucio (Phytotaxa, 2019)
Polyporus subpurpurascens is a rare Neotropical species characterized by deep purplish pilear surface and radially elongated pores. This study analyzed Neotropical specimens from Argentina, Bolivia and Brazil by applying detailed morphological examination and phylogenetic analyses. We conclude that P. subpurpurascens is a species of Neofavolus, and N. subpurpurascens is proposed as a new combination. New records from Argentina and Bolivia, a detailed description, and photographs of the species are included.